The two eyes of the Earth : art and ritual of kingship between Rome and Sasanian Iran - Canepa, Matthew P., 1975- (Berkeley : University of California Press, 2009)
This pioneering study examines a pivotal period in the history of Europe and the Near East. Spanning the ancient and medieval worlds, it investigates the shared ideal of sacred kingship that emerged in the late Roman and Persian empires. This shared ideal, while often generating conflict during the four centuries of the empires' coexistence (224-642), also drove exchange, especially the means and methods Roman and Persian sovereigns used to project their notions of universal rule: elaborate systems of ritual and their cultures' visual, architectural, and urban environments. Matthew Canepa expl.
Cover; Contents; Illustrations; Acknowlegments; Sources and Abbreviations; 1. Introduction; 2. The Art and Ritual of Kingship within and between Rome and Sasanian Iran; 3. The Lure of the Other and the Limits of the Past; 4. Sapur I, King of Kings of Iran and Non-Iran; 5. Rome's Troubled Third Century and the Emergence of a New Equilibrium; 6. Contested Images of Sacral Kingship and New Expressions of Triumph; 7. Unceasing Embassies; 8. City as Stage and Art as Statecraft; 9. The Late Antique Kosmos of Power; Epilogue; Notes; Bibliography; Index; Plates.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Rome -- Relations -- Iran; Iran -- Relations -- Rome; Rome -- Kings and rulers; Iran -- Kings and rulers; Monarchy -- Social aspects -- Rome; Monarchy -- Social aspects -- Iran; Rites and ceremonies -- Rome; Rites and ceremonies -- Iran; Romans -- Social life and customs; Sassanids -- Social life and customs; Rites et cérémonies -- Rome; Rites et cérémonies -- Iran; Romains -- Mœurs et coutumes; Sassanides -- Mœurs et coutumes; POLITICAL SCIENCE -- Globalization; HISTORY -- Ancient -- General; International relations; Kings and rulers; Manners and customs; Monarchy -- Social aspects; Rites and ceremonies; Romans -- Social life and customs; Iran; Rome (Empire); Koningschap; Apotheose (godsdienst); Symboliek; Uitwisseling; Iran; Romeinse rijk; ancient history; ancient rome; ancient societies; ancient world; art; byzantium; china; classical heritage; classical history; court life; engaging; europe; global politics; global powers; historical; iranian history; islam; kingship; medieval europe; medieval society; medieval times; near east; nonfiction study; persian empire; pivotal period; political history; roman empire; rome; royal intrigue; royalty